The effect of advertisement attractiveness and discounts on the purchase decision of Ms. Glow Beauty Products (study on ms. Glow consumers in jombang regency) - Krisdianto, Yusuf; Kurniawan, Indra (Institute of Computer Science (IOCS), 2025)
This study aims to determine and explain the Influence of Advertising Attraction and Discounts on Purchase Decisions for Ms. Glow Beauty Products (Study on Ms. Glow Consumers in Jombang Regency). Data collection using questionnaires to 100 consumers, the research approach used in the study is explanation. The analysis technique used is multiple linear regression through the assistance of the Statistical Package for Social Science (SPSS) application. Based on the results of the study, it shows that Advertising Attraction and Discounts have a significant effect on Purchase Decisions for Ms. Glow Beauty Products. Based on the results of the study, it shows that Advertising Attraction and Discounts have a significant effect on Purchase Decisions for Ms. Glow Beauty Products. Therefore, the higher the Advertising Attraction and Discounts, the higher the Purchase Decision for Ms. Glow Beauty Products